A construction method of visual conceptual scenario for hydrological conceptual modeling. (November 2021) - Wang, Jin; Chen, Min; Lü, Guonian; Yue, Songshan; Wen, Yongning; Sheng, Yehua; Lu, Mingyue
Abstract: With the increasing complexity of hydrological systems, hydrological modeling by modelers from different research areas has been regarded as an effective way to solve complex hydrological issues. As the first step of hydrological modeling, conceptual modeling plays an important role in supporting modeling idea communication among interdisciplinary modelers. Currently, conceptual modeling methods usually show the modeling ideas by using the block-based diagrams. However, further research need to be explored to express the spatial and temporal distribution of these modeling elements and their dynamic interaction relationships, thus promoting the communication of modeling ideas and reaching a common understanding of the modeling system among modelers. Visual conceptual scenario is the production of hydrological conceptual modeling and can be used to express modelers' cognition of modeling system. This article proposes a construction method of visual conceptual scenario. The conceptual component that represents the modeling elements, the rules that constrain the scenario construction, and a dynamic interaction method that supports the visualization of dynamic hydrological process are designed. Finally, a study case of identifying the impact of energy base water project on the groundwater is designed to illustrate the feasibility and practicability of the proposed construction method of visual conceptual scenario. Highlights: Visual conceptual scenario is a medium through which modeling cognition is expressed. Visual conceptual scenario can facilitate modeler's understanding of hydrological system. Modelers can exchange modeling ideas during the construction of conceptual scenario.